An investigation into NVC characteristics of vehicle behaviour using modal analysis - Hanouf, Zahir; Faris, Waleed Fekry; Ahmad, Kartini (Institute of Physics Publishing, 2017)
NVC characterizations of vehicle behavior is one essential part of the development targets in automotive industries. Therefore understanding dynamic behavior of each structural part of the vehicle is a major requirement in improving the NVC characteristics of a vehicle. The main focus of this research is to investigate structural dynamic behavior of a passenger car using modal analysis part by part technique and apply this method to derive the interior noise sources. In the first part of this work computational modal analysis part by part tests were carried out to identify the dynamic parameters of the passenger car. Finite elements models of the different parts of the car are constructed using VPG 3.2 software. Ls-Dyna pre and post processing was used to identify and analyze the dynamic behavior of each car components panels. These tests had successfully produced natural frequencies and their associated mode shapes of such panels like trunk, hood, roof and door panels. In the second part of this research, experimental modal analysis part by part is performed on the selected car panels to extract modal parameters namely frequencies and mode shapes. The study establishes the step-by-step procedures to carry out experimental modal analysis on the car structures, using single input excitation and multi-output responses (SIMO) technique. To ensure the validity of the results obtained by the previous method an inverse method was done by fixing the response and moving the excitation and the results found were absolutely the same. Finally, comparison between results obtained from both analyses showed good similarity in both frequencies and mode shapes. Conclusion drawn from this part of study was that modal analysis part-by-part can be strongly used to establish the dynamic characteristics of the whole car. Furthermore, the developed method is also can be used to show the relationship between structural vibration of the car panels and the passengers' noise comfort inside the cabin.